Association between Fragmented QRS Complex before Operation and a Trial Fibrillation after Coronary Artery Bypass Graft Surgery in Seyyedolshohada Hospital of Urmia - Reza Faramrzzadeh (Journal of Global Pharma Technology, 2017)
Introduction FQRS is defined as different patterns of fragmentation in wave R or wave S in narrow QRS complex and more than two R waves or more than one R wave in wide QRS complex. In various ischemic and non-ischemic diseases and non-hereditary and hereditary conduction diseases, FQRS has been examined. The predicting role of FQRS for a trial fibrillation (AF) after CABG that high incidence and associated with serious side effects in these patients has been examined only in one study. Methodology In this two-group study, 200 qualified patients who underwent CABG were included in the study. These patients were divided into two groups. One group received AF and other group did not receive AF. The incidence of AF after CABG and its association with FQRS were examined. In addition, the association of other variables with AF after CABG was examined using statistical software. Results Poet-operative AF was seen in 63 patients (25.2%) out of 250 patients. Patients with postoperative AF with had older age (P = 0.001) and larger left atrium (P =0.001). In patients with COPD, AF had more prevalence (P = 0.001). In addition, the extubation time of patient (P = 0.001) and heart on pump connection (0.001) were significantly associated with postoperative AF. FQRS (P = 0.001) and number of leads with FQRS (P = 0.001) were significantly associated with AF after CABG. However, patient gender, anemia, hypertension, diabetes mellitus, early detection of patients, number of vessels involved, the number of grafts, and graft to the right coronary artery, and the left main involvement were significantly associated with AF after CABG. Discussion In our study, postoperative AF is associated with presence of FQRS in ECG before operation in patients. In addition, FQRS has higher predictive value for postoperative AF. Keywords: AF, FQRS, CAB.